The Use Of Remote Sensing Data To Zoning Catchments In Flood Control Efforts Banjarbaru - Surya, Lalu Heriyadi; Ilham, Wahyuni; Agustina, Arfa; Susilawati, Susilawati (TROPICAL WETLAND JOURNAL, 2018)
This Research was occupied due to the frequent flood disaster in Indonesia especially in Banjarbaru city. South Kalimantan’s Research and Development Council in 2010 stated that the largest endangered flood are from spatially classification was Bangkal Village in Banjarbaru City. It became necessary to control by doing area zonation which determine the recharge area. This research was conducted survey method and data analysis by using information overlay from Geographic Information System. This research resulted the recommended recharge zone width was 2801,7 ha. In this research zone, the researchers gained 9 group of recharge zone and the development plan or activities to do. The researchers also configured some flooding potential classification, vary from 0,064 m/second to 0,078 m/second. The flooding water could be dried in at last 9,127 hours. The flood controlling efforts in settlement area biopores application and recharge wheel, for the water bodies were rivers normalization, planting trees or fruits and medical plants in buffer area. Social approach also could empowered the Bangkal Village Society with clean and sustainable environment competitions, environmental extension course about waste economic value and waste bank management.